Promoting Devotion to One's Work: The Servant Leader's Importance, What Motivates Workers, and Professional Ethics - Uray Ary Affandi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to determine the influence of servant leaders, work motivation, and work ethic on employee work commitment at PT. Famous Shoes Factory. This research approach is quantitative, using primary data obtained from 385 respondents. The analysis method uses multiple linear regression. The findings show that servant leaders have a significant positive effect on employee work commitment. However, the results are different in terms of work motivation and work ethic, which are unable to influence employee work commitment. However, if these three factors a role simultaneously, they can have a significant positive influence on the development of employee work commitment. This study provides new knowledge about the importance of serving leaders in leading companies. This research can rule out the role of work motivation and work ethic in creating work commitment. The implications of these research findings are significant for company leaders and academics for further research in building employee work commitment in a firm.